2014
DOI: 10.1071/bt14139
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depth-to-groundwater on structure and productivity of Eucalyptus woodlands

Abstract: Although it is well documented that access to groundwater can help plants survive drought in arid and semiarid areas, there have been few studies in mesic environments that have evaluated variation of vegetation characteristics across a naturally occurring gradient in depth-to-groundwater (DGW). The aim of this study was to determine whether differences in groundwater depth influence structural attributes and productivity of remnant woodlands in south-eastern Australia. The study area was located in the Kangal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 68 publications
4
37
0
Order By: Relevance
“…Ray parenchyma starch and nonstructural carbohydrates (NSCs) were collected during wet, drought, and rewatered periods. Plant characteristics including leaf area, tree height, and leaf temperature were measured using standard procedures (Palmer et al, ; Zolfaghar et al, ). Samples were collected during three periods: “Wet,” “Drought,” and “Re‐watered.” During the drought and rewatering treatments, plants received minimal water for 5–18 days until predawn leaf water potentials indicated plants were sufficiently stressed, and then, plants were rewatered to field capacity overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ray parenchyma starch and nonstructural carbohydrates (NSCs) were collected during wet, drought, and rewatered periods. Plant characteristics including leaf area, tree height, and leaf temperature were measured using standard procedures (Palmer et al, ; Zolfaghar et al, ). Samples were collected during three periods: “Wet,” “Drought,” and “Re‐watered.” During the drought and rewatering treatments, plants received minimal water for 5–18 days until predawn leaf water potentials indicated plants were sufficiently stressed, and then, plants were rewatered to field capacity overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Well‐watered leaf samples for each species were collected for plants before the drought was imposed and dried at 70°C for 72 hr. Three to four fully expanded, replicate leaves per species were ground and analyzed for the ratio of stable carbon 13 isotopes with Picarro G2101‐ i CO 2 analyser and Costech Combustion module (Picarro Inc.) Previously described methods were used (Zolfaghar et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Groundwater is the only available water resource for the vegetation's survival at the extremely arid zone in the northwest of China (Gries et al 2003). The previous studies found that the growth, distribution, and succession of riparian trees are closely related to the changes of groundwater depth (Aishan et al 2013;Gries et al 2003;Lammerts et al 2001;Zolfaghar et al 2014Zolfaghar et al , 2015. Researchers attach differences in groundwater depth to drought stress to study the physiological and morphological responses of riparian plants to investigate the adaptive traits (Chen et al 2003b(Chen et al , 2012Li et al 2013;Rzepecki et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Functional and structural attributes of vegetation often change in a predictable manner along gradients of water availability. For example, across sites with varying depth-to-groundwater, aboveground biomass and net primary productivity increased and water-use efficiency decreased as water availability increased (Zolfaghar et al, 2014). Water availability significantly influences rates of sap flow and annual rates of water use of trees (Dragoni, Caylor, & Schmid, 2009;Rossatto, Silva, Villalobos-Vega, Sternberg, & Franco, 2012;Whitley et al, 2013;Zeppel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%